Recent Advances in Mouse Models of Sjögren's Syndrome - Gao, Yunzhen; Chen, Yan; Zhang, Zhongjian; Yu, Xinhua; Zheng, Junfeng (Frontiers in Immunology, 2020)
Sjögren's syndrome (SS) is a complex rheumatoid disease that mainly affects exocrine glands, resulting in xerostomia (dry mouth) and xerophthalmia (dry eye). SS is characterized by autoantibodies, infiltration into exocrine glands, and ectopic expression of MHC II molecules on glandular epithelial cells. In contrast to the well-characterized clinical and immunological features, the etiology and pathogenesis of SS remain largely unknown. Animal models are powerful research tools for elucidating the pathogenesis of human diseases. To date, many mouse models of SS, including induced models, in which disease is induced in mice, and genetic models, in which mice spontaneously develop SS-like disease, have been established. These mouse models have provided new insight into the pathogenesis of SS. In this review, we aim to provide a comprehensive overview of recent advances in the field of experimental SS.